Africa?s big men
1 online resource (272 pages)
Keywords: This book spotlights, analyzes and explains varying forms and patterns of state-society relations on the African continent, taking as point of departure the complexities created by the emergence, proliferation and complicated interactions of so-called ?big men? across Africa's fifty-four states. The contributors interrogate the evolution of Africa?s big men; the role of the big men in Africa?s political and economic development; and the relationship between the state, the big men and the citizens.